2016
DOI: 10.1007/s12016-016-8548-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Viral Infections in Atopic Dermatitis: a Comprehensive Review

Abstract: Atopic dermatitis (AD) is the most common allergic skin disease in the general population. It is a chronic inflammatory skin disease complicated by recurrent bacterial and viral infections that, when left untreated, can lead to significant complications. The current article will review immunologic and molecular mechanisms underlying the propensity of AD patients to microbial infections. These infections include Staphylococcus aureus (S. aureus) skin infections, eczema herpeticum, eczema vaccinatum, and eczema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
203
1
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(234 citation statements)
references
References 78 publications
(83 reference statements)
9
203
1
21
Order By: Relevance
“…S. aureus colonization and impetiginization of the skin contribute to the exacerbation of skin inflammation in diseases such as AD, which has previously been attributed to the activity of S. aureus toxins and superantigens (Ong and Leung, 2016; Spaulding et al, 2013). In addition, studies in humans and mice have suggested that IL-1 family members ( i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus colonization and impetiginization of the skin contribute to the exacerbation of skin inflammation in diseases such as AD, which has previously been attributed to the activity of S. aureus toxins and superantigens (Ong and Leung, 2016; Spaulding et al, 2013). In addition, studies in humans and mice have suggested that IL-1 family members ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise etiology is not clear, AD is associated with a barrier defect in the skin, a dermal infiltration of T helper 2 (Th2) cells and a systemic Th2 cytokine response with elevated serum IgE and eosinophilia (Weidinger and Novak, 2016). S. aureus is linked to AD disease severity and flares (Kong et al, 2012) that have been attributed to S. aureus secreted toxins and superantigens (Ong and Leung, 2016; Spaulding et al, 2013). However, the immune signaling pathways that are activated during S. aureus epicutaneous exposure that contribute to skin inflammation are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Filaggrin (encoded by the gene FLG ) is a structural protein that is crucial to the formation of an intact normal skin barrier; it condenses keratin fibers from the cytoskeleton into tight clusters [25] and is crucial to maintaining the physical strength of the stratum corneum. Mature filaggrin is the result of proteolytic processing of the profilaggrin precursor, which also results in the release of peptides that are essential for skin homeostasis, e.g., natural moisturizing factor (NMF), and for maintenance of an acidic pH [26]. …”
Section: Barrier Function In the Skinmentioning
confidence: 99%
“…Interestingly, the CoNS strains that expressed AMPs were found to frequently colonize normal skin but were rarely detected on AD lesional skin [103••]. Furthermore, AD skin also exhibits decreased levels of keratinocyte-secreted AMPs [26, 104], which is correlated with increased S. aureus colonization [103••]. Recently, it was shown that the human AMP LL-37 when combined with antimicrobial peptides produced by the commensal Staphylococcus hominis can inhibit S. aureus survival more effectively than human or bacterial AMPs individually.…”
Section: Control Of Staphylococcal Colonization Of Skin By Antimicrobmentioning
confidence: 99%
See 1 more Smart Citation